System construction for comprehensive industrial ecosystem oriented networked collaborative manufacturing platform (NCMP) based on three chains. (April 2022) - Zhang, Xianyu; Ming, Xinguo; Bao, Yuguang; Liao, Xiaoqiang
Highlights: A system model for NCMP based on four perspectives is proposed. A system framework of NCMP based on three chains is proposed. Three collaborative subsystem of NCMP are constructed. A comprehensive system construction for NCMP in automobile industry is giving. It has a certain reference value for industry and government. Abstract: In industrial manufacturing, with the deep integration and development of advanced digital technologies such as industrial big data, industrial Internet and industrial artificial intelligence with manufacturing industry, the manufacturing model is gradually developing and evolving from the direction of networking, platform, integration, collaboration and ecology. Therefore, for industrial manufacturing process, the research of construction of comprehensive industrial ecosystem oriented Networked Collaborative Manufacturing Platform (NCMP) system is great industrial application value by integrating network characteristics, platform elements, integrated mechanism, collaborative model and ecological format. In this paper, the system model of NCMP is constructed from four perspectives, including network perspective, collaborative manufacturing perspective, platform perspective, and industrial ecosystem perspective. Then, a system framework of NCMP based on three chains (manufacturing chain, value chain, and industrial chain) is proposed. Three collaborative subsystems of NCMP (vertical collaboration subsystem from multi perspective, horizontal collaboration subsystem from multi process, end to end collaboration subsystem from multi operator) are constructed. At last, a comprehensive system construction for NCMP in automobile industry is giving. The research results show that the most important elements to construct NCMP are purchasing department collaboration, demand department collaboration, design collaboration, data integration between enterprises and factories, etc.